Solvolytic liquefaction of oil palm empty fruit bunch (EFB) fibres: analysis of product fractions using FTIR and pyrolysis-GCMS - Fei, Ling Pua; Sarani Zakaria; Chin, Hua Chia; Suet, Pin Fan; Rosenau, Thomas; Potthast, Antje; Liebner, Falk (Universiti Kebangsaan Malaysia, 2013)
Oil palm empty fruit bunch (EFB) fibers were subjected to solvolytic liquefaction to convert into liquid products using ethylene glycol (EG) as a supporting agent. The process was carried out at 250˚C for 60 min. The water-insoluble product fraction was exhaustively extracted with acetone (ASL fraction) to separate all less polar. FTIR and comparative analytical pyrolysis GC/MS of the parent EFB fiber and the ASL fraction confirmed the formation of larger amounts of long-chain lipophilic compounds under liquefaction conditions. Furthermore, a considerable amount of less polar thermal lignin degradation products were obtained comprising all of the three main lignin building blocks, i.e. 4-hydroxyphenyl- (P units), 4-hydroxy-3-methoxyphenyl- (G units) and 3,5-dimethoxy-4-hydroxyphenyl (S units) substituted compounds. 4-Prop-2-en-1-yl substituted phenolic compounds contributed mostly to the cumulated peak area of all lignin derived pyrolysis products obtained by analytical Curie point pyrolysis GC/MS at 600°C. The results of both instrumental-analytical methods confirm the formation of phenol and its derivatives, furan derivatives, organic acids, hydrocarbon, ester, benzene groups and alcohols.